(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: To determine the percentage of postmenopausal women ≥ 45 years old in Lam Dong province in 2023 who possess accurate knowledge regarding osteoporosis prevention and its relationship to bone density reduction. Research objects and methods: A cross-sectional study included 681 postmenopausal women ≥ 45 years old in Lam Dong province in 2023. Data were collected through direct interviews using a structured questionnaire. Results: Only 10.1% of postmenopausal women in Lam Dong province had accurate knowledge of osteoporosis prevention. The prevalence of bone density reduction in this group was 83.4%. Those with incorrect knowledge had a bone density reduction rate 3.38 times higher (95%CI: 1.97-5.81) than those with correct knowledge. Conclusions: Further research is needed to explore the relationship between osteoporosis prevention knowledge and bone density reduction. This will assist in developing effective interventions to lower disease rates and enhance the quality of life for high-risk individuals.